Short-term exposure to air pollution and biomarkers of cardiovascular effect: A repeated measures study. (15th June 2021) - Ni, Yu; Tracy, Russell P.; Cornell, Elaine; Kaufman, Joel D.; Szpiro, Adam A.; Campen, Matthew J.; Vedal, Sverre
Abstract: To help understand the pathophysiologic mechanisms linking air pollutants and cardiovascular disease (CVD), we employed a repeated measures design to investigate the associations of four short-term air pollution exposures – particulate matter less than 2.5 μm in diameter (PM2.5 ), nitrogen dioxide (NO2 ), ozone (O3 ) and sulfur dioxide (SO2 ), with two blood markers involved in vascular effects of oxidative stress, soluble lectin-like oxidized LDL receptor-1 (sLOX-1) and nitrite, using data from the Multi-Ethnic Study of Atherosclerosis (MESA). Seven hundred and forty participants with plasma sLOX-1 and nitrite measurements at three exams between 2002 and 2007 were included. Daily PM2.5, NO2, O3 and SO2 zero to seven days prior to blood draw were estimated from central monitors in six MESA regions, pre-adjusted using site-specific splines of meteorology and temporal trends, and an indicator for day of the week. Unconstrained distributed lag generalized estimating equations were used to estimate net effects over eight days with adjustment for sociodemographic and behavioral factors. The results showed that higher short-term concentrations of PM2.5, but not other pollutants, were associated with increased sLOX-1 analyzed both as a continuous outcome (percent change per interquartile increase: 16.36%, 95%CI: 0.1–35.26%) and dichotomized at the median (odds ratio per interquartile increase: 1.21, 95%CI: 1.01–1.44). The findings were not meaningfully changed after adjustment for additional covariates or in several sensitivity analyses. Pollutant concentrations were not associated with nitrite levels. This study extends earlier experimental findings of increased sLOX-1 levels following PM inhalation to a much larger population and at ambient concentrations. In light of its known mechanistic role in promoting vascular disease, sLOX-1 may be a suitable translational biomarker linking air pollutant exposures and cardiovascular outcomes. Graphical abstract: Image 1 Highlights: Short-term increases in PM2.5 were associated with increased sLOX-1 in an elderly population. Nitrite was not associated with any of the four pollutants – PM2.5, NO2, O3 and SO2 . sLOX-1 has a known mechanistic role in promoting vascular inflammation and CVD. The findings support the pathway linking PM2.5 with vascular inflammation and CVD. Abstract : In an elderly population, higher short-term PM2.5 concentrations were associated with increased sLOX-1, a translational biomarker linking air pollutant exposures and cardiovascular outcomes.